PENGARUH PENERAPAN STRATEGI BELAJAR PREVIEW, QUESTION, READ, REFLECT, RICETE, RIVIEW TERHADAP KETERAMPILAN MEMBACA SISWA SD - Ramadan, Arriyanti Rahayu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of the research is to analyse the effect of the usage of learning strategies preview, question, read, reflect, ricete, review on fifth grade child story reading students’ skills in 15th state elementary school in south Pontianak. The method that has been used was experiment method with forms of Pre-experimental design in the stake one group pretest posttest design. Research population of the entire fifth grad consists of 24 students in 15thstate elementary school in south Pontianak. The research sample was a class sample that is class fifth. Based on the result of data analysis, the mean of pre test was 63,26 and the mean of post test was 69,56. The hypothesis test result using t-test (Polled Variance) with dk 22 on 5 % significant level as known as table t = 1,717 obtained count (table t = 1,717). Then Ha accepted and Ho rejected. It could be conclude that there is an learning strategies preview, question, read, reflect, ricete, review on fifth grade child story reading students’ skills in 15th state elementary school in south Pontianak. The result of the calculation on the effect size is 1,02 (high criteria). It means that the usage of learning strategies preview, question, read, reflect, ricete, review gave high influence (effect) on fifth grade child story reading students’ skills in 15th state elementary school in south Pontianak. Keywords : Influence, preview, question, read, reflect, ricete, review, child story reading student’